The Trajectories That Remain to Be Told: Civic Participation, Immigrant Organizations, andWomen’s Leadership in Portugal - Topa, Joana (2023)
This study focuses on migrant women and their civic participation in civil society organizations and/or immigrant associations. Despite women’s migration having a long global history and being of academic interest, extensive knowledge of this situation has increased substantially in recent decades; research on the civic participation of immigrant women in Portugal is still incipient. The structural conditions affecting these women’s mobility processes remain overlooked, concealing their vulnerabilities. Additionally, success stories of migrant women, which could serve as inspirations for others, are often invisible. This exploratory research examines the role of female immigrant leaders and the demands they face in facilitating immigrants’ integration into Portuguese society. Eight qualitative interviews were conducted with diverse immigrant organizations in Portugal, advocating for immigrant rights and promoting integration through various strategies. The results reveal that migrant women’s experiences and participation in leadership roles are shaped not only by their migrant background and their qualifications but also by the difficulties they encountered upon arrival in Portugal. These leaders tend to focus on constraints, particularly regarding the organization’s sustainability, rather than emphasizing opportunities for civic participation. Nevertheless, this study also reveals that participation in IOs leads to increased autonomy and a heightened sense of empowerment for these women. It grants them a voice, visibility, and recognition both in the host society and their own communities. Overall, the study sheds light on the significance of recognizing immigrant women’s contributions and challenges, as well as the crucial role played by immigrant organizations in promoting integration and advocating for immigrants’ rights in Portugal. It also emphasizes the need for the government to financially support these organizations.